2021
DOI: 10.1590/2177-6709.26.2.e212020.oar
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluoride on mechanical properties of NiTi and CuNiTi orthodontic archwires: an in vitro study

Abstract: Introduction: After debonding, white spot may appear on the area below the bracket, which is the early clinical sign of carious lesion. There is increased caries risk underneath and adjacent to orthodontic bands and brackets, which call for maximum use of caries preventive procedures using various fluoride application methods. Objective: The aim of the study was to evaluate alterations in the mechanical properties (modulus of elasticity and yield strength) in loading and unloading phases for different orthodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Previous studies showed that fluoride affected titanium‐containing archwires more, leading to a higher surface roughness due to a decreased corrosion resistance of the archwire, 15,24,35–37 which agrees with our findings. Also, one study found that routine fluoride application affected the mechanical properties of orthodontic archwires containing titanium, 38 which was further explained in another study as being a factor of hydrogen embrittlement of the alloy 36 . On the other hand, a study tested the effect of mechanical brushing on the surface wear of StSt wires.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies showed that fluoride affected titanium‐containing archwires more, leading to a higher surface roughness due to a decreased corrosion resistance of the archwire, 15,24,35–37 which agrees with our findings. Also, one study found that routine fluoride application affected the mechanical properties of orthodontic archwires containing titanium, 38 which was further explained in another study as being a factor of hydrogen embrittlement of the alloy 36 . On the other hand, a study tested the effect of mechanical brushing on the surface wear of StSt wires.…”
Section: Discussionmentioning
confidence: 97%
“…While demineralization prevention using fluoride may be considered, there is no clear evidence of its effectiveness [ 57 ]. Furthermore, acidulated phosphate fluoride reduces Ni-Ti strength [ 58 ]. Therefore, new approaches are required.…”
Section: Discussionmentioning
confidence: 99%